The blame game - Jones, Sandie (St. Martin's Paperbacks, 2024)
As a psychologist specializing in domestic abuse, Naomi has found it hard to avoid becoming overly invested in her clients' lives. But after helping Jacob make the decision to leave his wife, Naomi worries that she's taken things too far. Then Jacob goes missing, and her files on him vanish.... But as the police start asking questions about Jacob, Naomi's own dark past emerges. And as the truth comes to light, it seems that it's not just her clients who are in danger.